PRISON EDUCATION AND TRAINING IN JORDAN - Khawla Ahmad Hussein Otoom (International Journal of Advanced Science and Technology, 2020)
Prison Education entails any educational activity which takes place within the prison to aid in developing the prisoners. Its courses can include basic literacy programs, secondary school equivalency programs, vocational education and tertiary education. Other activities such as rehabilitation programs, physical education and arts and crafts programs may also be considered a form of prison education. Programs are typically provided, managed and funded by the prison system, though inmates may be required to pay for distance education programs. This study is one of very few research-based investigations regarding prison education and training in Jordan. The result shows that the education programs are targeted at 5 trends since year 2000 in Jordan which include the first trend is literacy for the uneducated,. the second is the educational level and the completion of general secondary examination, the third trend, tertiary education and postgraduate, the fourth trend, vocational training, fifth trend, general culture programs: it is the implementation of evening programs on a certain range of inmates, who have acceptable academic levels, and enter into cultural programs, or learn foreign languages, or computer skills, the number of inmates who have passed English courses in Jordan in 2017 (185) prisoners, the number of inmates who entered the computer courses (55), the evening courses in accounting and hotel business (66), and is the decade of many cultural seasons in a number of reform centers included programs in the field of human rights and family protection , drug control, attended by lecturers, specialists from various official bodies concerned it should be noted that the majority of the reforming and rehabilitation centers also provide cultural and information and knowledge management, 2018. It was concluded that the rights of prisoners to access education and training are recognized both national and international level, moreover, the provision of learning opportunities in prison presents an important part of the rehabilitation process and can help inmates to make good use of their sentence as well as presenting a second chances to gain skills and qualifications which may help them to find employment, pursue further education and training opportunities or simply to better manage or cope with their lives on releases. However, this was contrary to the findings which shows that prisoners in Jordan are more expose to hard torture than been train and educated. Therefore, there is more need to promote prison education and training in Jordan.